INNOVATION IN PEDAGOGICAL PRACTICES: TECHNOLOGY-ENHANCED LEARNING IN HIGHER EDUCATION - Kusum Lata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of technology in higher education has transformed pedagogical practices, facilitating a shift from traditional teaching methods to more dynamic, interactive, and personalized learning experiences. This paper explores the innovations in pedagogical practices driven by technology-enhanced learning (TEL). It examines the impact of TEL on student engagement, learning outcomes, and teaching methodologies, while also addressing challenges and future directions for implementation in higher education.